2016
DOI: 10.1192/bjp.bp.114.156554
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and new onset of cardiovascular disease: critical review and meta-analysis

Abstract: Anxiety may be of interest for CVD prevention. Future research should examine biological and behavioural underpinnings of the association in order to identify targets for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
141
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(152 citation statements)
references
References 112 publications
5
141
0
6
Order By: Relevance
“…Poor baseline psychological health has been implicated in the onset and/or exacerbation of other health conditions such as hypertension 27 , metabolic syndrome 28 , CVD 29 , mild cognitive impairment 30 , and general pain 31 . However, in the present study, baseline wellbeing and depression were not significant predictors of pain change after 6 mo of ATORVA and do not appear to be associated with SAMS in otherwise healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Poor baseline psychological health has been implicated in the onset and/or exacerbation of other health conditions such as hypertension 27 , metabolic syndrome 28 , CVD 29 , mild cognitive impairment 30 , and general pain 31 . However, in the present study, baseline wellbeing and depression were not significant predictors of pain change after 6 mo of ATORVA and do not appear to be associated with SAMS in otherwise healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that other facets of psychological stress, namely anxiety and hostility/anger, have been associated with an increased risk of cardiovascular disease, independent of traditional cardiovascular disease risk factors and depression 18 , and confer increased risks of myocardial infarction or death among patients with established cardiovascular disease 19,20 . Our data suggests that while depression after cardiac rehabilitation is rare, when present, it is often associated with other psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established a prospective association between anxiety disorders and IHD,7 8 and there is evidence of a causal association between anxiety and cardiovascular diseases 9. Findings from the Norwegian longitudinal Nord-Trøndelag Health Study (HUNT) suggest a possible dose–response pattern between anxiety, measured by the anxiety subscale of the Hospital Anxiety and Depression Scale, and incident myocardial infarction 23.…”
Section: Discussionmentioning
confidence: 99%